POTENSI DAYA TARIK DAN STRATEGI PENGEMBANGAN PULAU BAER SEBAGAI OBJEK WISATA ALAM DI DESA DULLAH LAUT KOTA TUAL - Reynaldo Madubun; Yosevita.Th Latupapua (JURNAL HUTAN PULAU-PULAU KECIL, 2021)
This study aims to examine the internal factors and external factors that influence the development of the object of attraction of the island of Baer and how the strategy for developing the potential of the island of Baer. Methods of data collection using observation, interviews and filling out questionnaires to the community respondents as many as 25 respondents, and 4 key actors. The analysis used is a SWOT analysis (strengths, weaknesses, opportunities, threats). The analysis results obtained explain that the average total internal factor score of 1.96 is in the low category, where the strength score is 2.3 and the weakness score is 1.62. While the average total score of 1.08 external factors is on a low scale, where the opportunity score is 1.3, and the threat score is 0.87. The results of the analysis show that the potential of Baer Island has the opportunity for aggressive development (quadrant I) with the strategy that must be carried out is to develop optimally the potential of flora-fauna, natural panorama and, improve the quality of tourism objects by procuring supporting facilities and infrastructure packaged in tour packages, and requires active participation of all stakeholders.